A REFLECTION ON PUBLIC POLICIES IN COMBATING TUBERCULOSIS. A WORLDWIDE PANORAMA - Gomes Abreu, Abraão; Almeida Sarmento, Carolyne; Paulo da Silva, Carlos; da Conceição Nascimento, Daniel; Aguiar Moulaz, Gabriel; Gabriel Palma Pereira, José; Gilkla da Silva Abreu, Glenya; Aparecida da Silva, Juliana; Hannya Campos Gazola, Larissa; de Oliveira Mussi, Leonardo; Cristina Barbosa Serejo, Letícia; Sandy Barbosa de Lima, Lindsay; et al. (Health and Society, 2024)
A reflection on public policies to combat Tuberculosis. A global panorama Tuberculosis is an infectious bacterial disease caused by Mycobacterium tuberculosis, mainly affecting the lungs and transmitted from person to person through respiratory droplets. Although the infection does not always cause symptoms in healthy people, when active, it can cause coughing, chest pain, weakness, weight loss and fever. Tuberculosis is currently a global health concern, with millions of deaths and new infections each year, due to factors such as drug resistance, HIV, international travel and homelessness. With a third of the world’s population infected, it is essential that healthcare professionals understand the disease and its diagnostic procedures. New research should focus on the social factors that determine TB. In this way, it is believed, Brazil will once again be able to celebrate reaching the WHO targets for the elimination of TB by 2035.